2000
DOI: 10.1152/ajpcell.2000.278.3.c601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Pi regulation of the skeletal muscle SR Ca2+ release channel

Abstract: Inorganic phosphate (P(i)) accumulates in the fibers of actively working muscle where it acts at various sites to modulate contraction. To characterize the role of P(i) as a regulator of the sarcoplasmic reticulum (SR) calcium (Ca(2+)) release channel, we examined the action of P(i) on purified SR Ca(2+) release channels, isolated SR vesicles, and skinned skeletal muscle fibers. In single channel studies, addition of P(i) to the cis chamber increased single channel open probability (P(o); 0.079 +/- 0.020 in 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…3C) (WT% initial ⌬F/F0 ϭ 5.0 Ϯ 3.0%, n ϭ 5; KO ϭ 3.3 Ϯ 1.1%, n ϭ 9; P ϭ 0.53). This initial facilitation of tetanic Ca 2ϩ transient amplitude is consistent with previous single fiber analyses of repetitive stimulation (5) and is generally attributed to elevated inorganic phosphate initially stimulating release (4,8). WT fibers then sustained maximal tetanic amplitude for a longer duration than KO fibers, after which both WT and KO fibers eventually showed a consistent decline in train amplitude (Fig.…”
Section: Ap-initiated Casupporting
confidence: 89%
“…3C) (WT% initial ⌬F/F0 ϭ 5.0 Ϯ 3.0%, n ϭ 5; KO ϭ 3.3 Ϯ 1.1%, n ϭ 9; P ϭ 0.53). This initial facilitation of tetanic Ca 2ϩ transient amplitude is consistent with previous single fiber analyses of repetitive stimulation (5) and is generally attributed to elevated inorganic phosphate initially stimulating release (4,8). WT fibers then sustained maximal tetanic amplitude for a longer duration than KO fibers, after which both WT and KO fibers eventually showed a consistent decline in train amplitude (Fig.…”
Section: Ap-initiated Casupporting
confidence: 89%
“…ST fibers already have a reduced rate of Ca 2ϩ release, force production, and relaxation rate (3,5). As mentioned above, Fig.…”
Section: Physiological Relevancementioning
confidence: 59%
“…Second, P i might act on the RyR and increase SR Ca 2ϩ release. Accordingly, elevated P i has been shown to increase the open probability of isolated RyR incorporated into lipid bilayers as well as the rate of Ca 2ϩ -induced Ca 2ϩ release in SR vesicles and skinned fibers (27,174). However, it has since been shown that P i decreases caffeine-and depolarization-induced SR Ca 2ϩ release in mechanically skinned rat skeletal muscle fibers in a Mg 2ϩ -dependent manner (135).…”
Section: P I and The Increase Of Tetanic [Ca 2ϩ ] I In Early Fatiguementioning
confidence: 99%